Perfluorooctane sulfonic acid (PFOS) adsorbed to polyethylene microplastics: Accumulation and ecotoxicological effects in the clam Scrobicularia plana. (February 2021) - Islam, Naimul; Garcia da Fonseca, Tainá; Vilke, Juliano; Gonçalves, Joanna M.; Pedro, Paulo; Keiter, Steffen; Cunha, Sara C.; Fernandes, José O.; Bebianno, M.J.
Abstract: Microplastics are widespread in the marine environment, whereby the uptake of these tiny particles by organisms, can cause adverse biological responses. Plastic debris also act as a vector of many contaminants, herein depending on type, size, shape and chemical properties, possibly intensifying their effects on marine organisms. This study aimed to assess the accumulation and potential toxicity of different sizes of microplastics with and without adsorbed perfluorooctane sulfonic acid (PFOS) in the clam Scrobicularia plana . Clams were exposed to low-density polyethylene microplastics (1 mg L −1 ) of two different sizes (4–6 and 20–25 μm) virgin and contaminated with PFOS (55.7 ± 5.3 and 46.1 ± 2.9 μg g −1 respectively) over 14 days. Microplastic ingestion, PFOS accumulation and filtration rate were determined along with a multi biomarker approach to assess the biological effects of microplastics ingestion. Biomarkers include oxidative stress (superoxide dismutase, catalase, glutathione peroxidases), biotransformation enzymes (glutathione-S-transferases activity), neurotoxicity (acetylcholinesterase activity), oxidative damage and apoptosis. Microplastics ingestion and PFOS accumulation was microplastic size dependent but not PFOS dependent and filtration rate was reduced at the end of the exposure. Reactive oxygen species in gills and digestive gland were generated as a result of exposure to both types of microplastics, confirming the disturbance of the antioxidant system. Larger virgin microparticles lead to stronger impacts, when compared to smaller ones which was also supported by the Integrated Biomarker Responses index calculated for both tissues. An anti-apoptotic response was detected in digestive glands under exposure to any of the MPs treatments. Highlights: Low density polyethylene virgin MPs and with PFOs adsorbed of two different sizes were ingested in Scrobicularia plana . MPs act as a vector of PFOS in S. plana tissues and PFOS accumulation was independent of MPs size. Higher MPs accumulation was in the clams exposed to the bigger size of virgin LDPE MPs. Oxidative stress was MPs size and tissue dependent.